Perancangan Antarmuka Aplikasi Penyewaan Florist Menggunakan Metode Design Thinking - Real Ananda Kristi; Prisa Marga Kusumantara; Nur Cahyo Wibowo (Lembaga Pengembangan Kinerja Dosen, 2023)
In today's era, the florist industry has evolved, offering a variety of products such as flower bouquets, floral arrangements, flower boards, and single flowers, both real and artificial. However, the process of ordering or renting florist services is currently inefficient. Therefore, the objective of this research is to design a mobile-based florist rental application using the Design Thinking method, with a focus on achieving excellent usability. Testing was conducted, resulting in a final effectiveness score of 94.54% and an efficiency score of 95.84%, both falling into the category of good or excellent. Additionally, in the satisfaction aspect, a final score of 81.8 was achieved, categorizing it as good and acceptable.